Integration of Digital Skills in the Accounting Education Curriculum: A Literature Review and Curriculum Development Recommendations - Lidyawati, Linda; Sriyanto, Agus; Mentalita, Hotma; Aritonang, Romulo Parlindungan; DS, Hotman (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The rapid advancement of digital technologies is transforming the accounting profession at an unprecedented pace, creating substantial gaps between the skills demanded by employers and those cultivated within existing accounting education curricula. This study explores the extent to which digital skills are integrated into accounting education curricula and identifies strategies for curriculum enhancement. Employing a systematic literature review methodology, this research synthesized 25 peer-reviewed articles and academic books published between 2015 and 2024, sourced from Scopus, Web of Science, and Google Scholar databases. The findings reveal four dominant themes: (1) a significant misalignment between academic curricula and industry digital skill requirements; (2) emerging consensus on essential digital competencies for future accountants, including data analytics, cloud computing, and artificial intelligence literacy; (3) institutional barriers to curriculum reform such as faculty digital competency limitations and resource constraints; and (4) best practices in integrating digital skills through competency-based frameworks. This study proposes a structured conceptual framework for integrating digital skills into accounting education curricula, offering actionable recommendations for educators, curriculum designers, and institutional policymakers. The findings carry significant implications for accounting education reform in both developing and developed countries, particularly in the context of Industry 4.0 and the post-pandemic digital acceleration.